Arthur St. Clair papers - St. Clair, Arthur, 1734-1818.
Sheriff's writ (1774 July 7) from Westmoreland County, Pa.; decree (1788 Aug. 30) establishing a general court for the Northwest Territory at Marietta, Ohio; photocopy of St. Clair's presidential appointment (1789 Sept. 1) by George Washington as governor of the Northwest Territory; and ALS from St. Clair to Benjamin Talmadge relating to Ohio Company land warrants.
In part, negative photocopy.
Delegate to the Continental Congress from Pennsylvania, army officer, and governor of the Northwest Territory.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Talmadge, Benjamin -- Correspondence; Washington, George, -- 1732-1799.; Ohio Company (1786-1795); Courts -- Northwest Territory; Land titles -- Ohio; Sheriffs -- Pennsylvania -- Westmoreland County; Marietta (Ohio) -- History; Northwest Territory -- Politics and government; Ohio -- History -- 1787-1865.; Pennsylvania -- History -- Colonial period, ca. 1600-1775.; Westmoreland County (Pa.) -- History; Army officers; Delegates, U.S. Continental Congress -- Pennsylvania; Governors -- Northwest Territory